Integrated Model of Drugs Addictive Client Spirituality Development - Arip Sentosa; Raihan Raihan; Attabik Lutfi (Yayasan Ilomata, 2023)
This research is motivated by the rise of drug trafficking from the elite to the grassroots, so that many people are trapped and fall into drug addicts. They need recovery and support to rise to normal human beings. So, how is the design of coaching that can touch the physical and mental recovery and spiritual recovery of addicts in recovery. To answer this question, researchers conducted a comparative study at the National Narcotics Rehabilitation Center, Lido with the Suryalaya Islamic Boarding School, Tasikmalaya, West Java. This study uses a qualitative phenomenological approach, namely the Interactive Analysis and Comparative Analysis models. Extracting the data of this research seeks to reveal and see the development of addicts through the two sides of the Institute by way of interviews, observation and documentation, which are then analyzed, as well as reducing the data to be interpreted and described. The results of the research and writing of this dissertation are expected to give birth to a design model in handling drug addict client development that can touch physical, psychological, mental and spiritual recovery. A design model that integrates medical treatment of medicine and religious therapy which are integrated into a coaching system.